A Preliminary Report on Disordered Speech with Deep Brain Stimulation in Individuals with Parkinson's Disease - Christopher Dromey; Suzy Bjarnason (Parkinson's Disease)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) has proven effective in treating the major motor symptoms of advanced Parkinson's disease (PD). The aim of this study was to learn which laryngeal and articulatory acoustic features changed in patients who were reported to have worse speech with stimulation. Six volunteers with PD who had bilateral STN electrodes were recorded with DBS turned on or off. Perceptual ratings reflected poorer speech performance with DBS on. Acoustic measures of articulation (corner vowel formants, diphthong slopes, and a spirantization index) and phonation (perturbation, long-term average spectrum) as well as verbal fluency scores showed mixed results with DBS. Some speakers improved while others became worse on individual measures. The magnitude of DBS effects was not predictable based on the patients' demographic characteristics. Future research involving adjustments to stimulator settings or electrode placement may be beneficial in limiting the negative effects of DBS on speech.